Odpowiedzi

Najlepsza Odpowiedź!
2010-02-06T11:59:35+01:00
A)
Pc = 2πrH + πr²

Pc₁= 2πr(H+2) + πr²
Pc₁= 2πrH + 4πr + πr²

2πrH + 4πr + πr² - 2πrH - πr² = 4πr
_____________________________________

V = Hπr²

V₁= πr²(H+2)
V₁= Hπr² + 2πr²

Hπr² + 2πr² - Hπr² = 2πr²
_____________________________________
b)
Pc = 2πrH + πr²

Pc₁= 2π(r+2)H + π(r+2)²
Pc₁= 2πrH + 4πrH + π(r²+4r+4)
Pc₁= 2πrH + 4πrH + πr²+4πr+4π

2πrH + 4πrH + πr²+4πr+4π - 2πrH - πr² = 4πrH + 4πr
_____________________________________

V = Hπr²

V₁= π(r+2)²H
V₁= π(r²+4r+4)H
V₁= Hπr² + 4Hπr + 4Hπ

Hπr² + 4Hπr + 4Hπ - Hπr² = 4Hπr + 4Hπ